A Survey for the Evaluation of Faculty Trainings on Designing E-courses for the University Faculty Members' Skill Enhancement. (3rd October 2017) - Alenezi, Ahmed Maajoon
ABSTRACT: This research is an outcome of trainings conducted and their implementation to use content authoring tools in e-learning environment. Male and female faculty members from Saudi Arabia's Northern Border University (NBU), with varied levels of awareness and exposures into e-learning system, represented different colleges and campuses. They were encouraged to create and practice authoring tools after the advanced trainings. Dramatic improvement was observed among the participants to develop resourceful courses. Evaluation was done to record improvements for changes in the competency level. This paper assesses how trainings changed their awareness level and skills to use designing tools to develop coursers for e-learning. They found it as an innovative tool to create the courses. This paper highlights the general awareness and skills of faculty members towards e-learning and course designing tools. It assesses awareness and skills of users for their adaptability towards course designing and the use of respective tools after trainings.